2013
DOI: 10.1056/nejmoa1208200
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-Balloon Time and Mortality among Patients Undergoing Primary PCI

Abstract: Although national door-to-balloon times have improved significantly for patients undergoing primary PCI for ST-segment elevation myocardial infarction, in-hospital mortality has remained virtually unchanged. These data suggest that additional strategies are needed to reduce in-hospital mortality in this population. (Funded by the National Cardiovascular Data Registry of the American College of Cardiology Foundation.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
342
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 624 publications
(395 citation statements)
references
References 24 publications
26
342
3
5
Order By: Relevance
“…Meenes et al8 have shown that further reduction in D2B times have not resulted in decreased mortality in patients with STEMI. It appears that it is prudent to shift focus to prehospital care to investigate how C2D times can be shortened, which will improve survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Meenes et al8 have shown that further reduction in D2B times have not resulted in decreased mortality in patients with STEMI. It appears that it is prudent to shift focus to prehospital care to investigate how C2D times can be shortened, which will improve survival.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that reducing D2B times beyond this 90‐minute benchmark has not resulted in decreased mortality; notably, mortality from STEMI has plateaued with further reductions in D2B. Menees et al8 have demonstrated a 20% reduction in D2B times from 83 minutes in 2005, with no effect on mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines for the treatment of ST‐segment elevation myocardial infarction recommend a door‐to‐balloon time of 90 min or less for patients undergoing percutaneous coronary intervention;9, 10, 11 therefore, the shortening of the door‐to‐balloon time after introduction of JTAS is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is important to assess how long the door‐to‐balloon time has shortened since the introduction of JTAS for patients with acute coronary syndrome, such as ST‐elevated myocardial infarction 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Recently, although the door‐to‐balloon time has improved significantly for patients undergoing primary percutaneous coronary intervention (PCI) for an acute myocardial infarction (AMI), the in‐hospital mortality has remained virtually unchanged 1. Implantable cardioverter defibrillators (ICDs) have been widely recognized as effective devices for preventing sudden cardiac death from fatal arrhythmias 2, 3.…”
Section: Introductionmentioning
confidence: 99%